Penerapan Media Pembelajaran Fotonovela Pada Materi Pencemaran Lingkungan Untuk Siswa - Supriyanto, Gege Chandra; Bukhori, Imam (JURNAL BIOSHELL, 2021)
Learning Media always consists of two important elements, namely elements of equipment for hardware and elements of the message it carries(message/software). Based on interview, obtained the application of learning media photonovela. This research categorized in classroom action research. Data analysis is quantitative, while the data collection method was obtained from the test (LKS) which applied the photonovela learning media and the cycle test. This study aims to apply the photonovela learning media with environmental pollution learning materials. With 21 research subjects. The data obtained from the results of the number of tests in the first cycle was 1622 and decreased to 1372 in the second cycle. The data obtained from the results of classical completeness in the first cycle 71% and decreased to 29% in the second cycle. The data obtained from the average value of one class in the first cycle was 77 and decreased to 65 in the second cycle. This proves that the application of the photonovela learning media still requires correction in terms of application. Keywords : Photonovela learning media, Number of test results, Classical completeness results, One class average score.